Changes In Phenolic Content And Antioxidant Activity During Traditional Fermentationof Bamboo Shoot Of Noney District, Manipur, India. (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Bamboo (Bambusa balcooa) is a plant that is widely distributed and grows in the valley and hilly areas of Manipur, a state located in the northeastern part of India. Young and tender bamboo shoot is consumed in fresh or fermented form, locally called soibum. In Manipur, there are two different modes of fermentation; Andro type and Noney /Kwatha type. Aim: The study aimed to investigate the changes in phenolic and flavonoid contents and antioxidant activity during traditional fermentation of bamboo shoots collected from Noney District of Manipur, a northeastern state of India. Materials and methods: Raw and fermented bamboo shoots extracts were prepared by using 80% (v/v) ethanol for evaluation of total phenolic content by Folin-Ciocalteau reagent method and total flavonoid content by aluminium chloride colorimetric method and methanol 80%(v/v) for antioxidant activity by using DPPH radical assay.Results: The fermented bamboo shoots showed a high level of phenolic contents, flavonoid contents, and antioxidant activity. The 60days fermented had the highest phenolic contents of 238.33 mg CE/100g and the highest flavonoid contents of 32.32 mg QE/100g, while the 25 -day fermented sample had the highest level of antioxidant activity of 32.77%. Conclusion: The study can conclude that consumption of fermentedshoots of Bambusa balcooa could be more beneficial to our health than raw one as it has more level of antioxidant activity and polyphenols.